Methylglyoxal Requires AC1 and TRPA1 to Produce Pain and Spinal Neuron Activation - Griggs, Ryan B.; Laird, Don E.; Donahue, Renee R.; Fu, Weisi; Taylor, Bradley K. (Frontiers in Neuroscience, 2017)
Methylglyoxal (MG) is a metabolite of glucose that may contribute to peripheral neuropathy and pain in diabetic patients. MG increases intracellular calcium in sensory neurons and produces behavioral nociception via the cation channel transient receptor potential ankyrin 1 (TRPA1). However, rigorous characterization of an animal model of methylglyoxal-evoked pain is needed, including testing whether methylglyoxal promotes negative pain affect. Furthermore, it remains unknown whether methylglyoxal is sufficient to activate neurons in the spinal cord dorsal horn, whether this requires TRPA1, and if the calcium-sensitive adenylyl cyclase 1 isoform (AC1) contributes to MG-evoked pain. We administered intraplantar methylglyoxal and then evaluated immunohistochemical phosphorylation of extracellular signal-regulated kinase (p-ERK) and multiple pain-like behaviors in wildtype rats and mice and after disruption of either TRPA1 or AC1. Methylglyoxal produced conditioned place avoidance (a measure of affective pain), dose-dependent licking and lifting nociceptive behaviors, hyperalgesia to heat and mechanical stimulation, and p-ERK in the spinal cord dorsal horn. TRPA1 knockout or intrathecal administration of a TRPA1 antagonist (HC030031) attenuated methylglyoxal-evoked p-ERK, nociception, and hyperalgesia. AC1 knockout abolished hyperalgesia but not nociceptive behaviors. These results indicate that intraplantar administration of methylglyoxal recapitulates multiple signs of painful diabetic neuropathy found in animal models of or patients with diabetes, including the activation of spinal nociresponsive neurons and the potential involvement of a TRPA1-AC1 sensitization mechanism. We conclude that administration of MG is a valuable model for investigating both peripheral and central components of a MG-TRPA1-AC1 pathway that contribute to painful diabetic neuropathy.